2012
DOI: 10.1007/s10388-012-0312-1
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of docetaxel/cisplatin/5-fluorouracil preoperative combination chemotherapy in esophageal cancer patients with extended lymph node metastases

Abstract: Aim We retrospectively investigated the efficacy and safety of combination chemotherapy with 5-fluorouracil (5-FU) and cisplatin plus docetaxel (DCF) as preoperative chemotherapy. Methods One hundred and seven patients were diagnosed with esophageal cancer of clinical stage II and III (except T4) from March 2007 to June 2009. Among these, five patients who had extensive locoregional lymph node metastases underwent preoperative DCF chemotherapy. Results Median age of the five patients was 59 (51-67) years, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2013
2013
2014
2014

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…[3][4][5] A novel regimen that consists of docetaxel, cisplatin, and 5-FU (DCF) is a candidate for NAC against SCCE. 6,7 The superiority of this regimen to FP has already been reported with regard to head and neck cancer, which is biologically similar to SCCE. 8,9 We previously reported the results of 51 patients who received DCF as preoperative chemotherapy (PCT) against SCCE.…”
Section: Introductionmentioning
confidence: 70%
See 4 more Smart Citations
“…[3][4][5] A novel regimen that consists of docetaxel, cisplatin, and 5-FU (DCF) is a candidate for NAC against SCCE. 6,7 The superiority of this regimen to FP has already been reported with regard to head and neck cancer, which is biologically similar to SCCE. 8,9 We previously reported the results of 51 patients who received DCF as preoperative chemotherapy (PCT) against SCCE.…”
Section: Introductionmentioning
confidence: 70%
“…Tanaka et al reported on DCF as NAC for five SCCE patients with clinical stage III disease. 6 The clinical response rate and pathological response rate, defined as a histological response of ≥grade 1b, were both as high as 80%. Watanabe et al 7 reported that the clinical response rate and pathological complete response rate were 60.8% and 11.1%, respectively.…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations